Role of Cell Block Technology as an Adjunct to Fine Needle Aspiration in Evaluating as well as Differentiating Liver Lesions - Sujata Mallick; Mahasweta Mallik; Rabindra Chatterjee; Puskar Chowdhury (Iranian Society of Pathology, 2021)
Background & Objective: Liver lesions are difficult to diagnose and to differentiate primary from metastatic carcinoma, while Biopsy has its limitations. Cell block technology is easily accessible with high diagnostic accuracy. Our aim is 1) To find the role of cell block technology as an alternative to biopsy in identifying liver lesions; 2) To find the efficacy of cell block along with immunohistochemistry (IHC) and ancillary studies in differentiating primary from metastatic lesions; 3) To identify the site of origin of metastatic lesions. This is a descriptive study undertaken in two tertiary care hospitals over a period of three years.Methods: Retrospective review of adequate samples from fine needle aspirations from liver lesions under radiological coverage, converted into cell block was done. IHC was applied as needed. Usefulness of cell block preparation was evaluated, and the final diagnosis correlated with the biopsy results.Results: Analysis of 323 cases found sensitivity of 98.75% and positive predictive value of 99% for all lesions. Sensitivity for metastatic carcinomas was slightly more than hepatocellular carcinoma. However, accuracy of cell block results for individual metastatic lesions and site of origin was less. IHC and morphological pattern worked as an important adjunct in the final diagnosis. On the other hand, contribution of viral markers as a supplement in the final work up was ambiguous. Conclusion: High precision of validity results of cell block technology in comparison with biopsy highlights its pivotal role in conjunction with supportive tests for diagnosing and differentiating liver lesions as well as identifying primary sites in liver metastasis.